Tirzepatide - role in obesity, health and physical wellness. Information overview - Hanslik, Anna; Mendak, Magdalena; Białek, Agata; Walczak, Agnieszka; Hovagimyan, Adrian; Olszanecka, Monika; Olszanecki, Tomasz (Quality in Sport, 2025)
Nowadays there is an increasing number of people with overweight and obesity all around the world. Unhealthy food, sweets and fast foods are available everywhere, that causes self-perpetuating problem. Food restriction is an obvious treatment, but it is difficult to achieve. A certain solution are GLP-1 agonists using to treat type 2 diabetes. Last studies shown that that medicaments may be effective in promoting weight loss. Tirzepatide as a novelty and is a long-acting dual agonist of glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-1 (GLP-1) receptors. It can be very supportive in the fight against obesity.